1997
DOI: 10.1111/j.1432-1033.1997.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Channeling of Intermediates in the Oxidative Pentose Phosphate Pathway by Soybean and Pea Nodule Extracts, Yeast Extracts, and Purified Yeast Enzymes

Abstract: Evidence is presented that intermediates of the oxidative pentose phosphate pathway (OPPP) are channeled from one pathway enzyme to the next. CO, produced from [l-'4C]glucose in the presence of unlabelled pathway intermediates contained much more radioactivity than predicted by a model in which pathway-produced intermediates are in equilibrium with identical molecules in the bulk phase. This was the case whether glucose 6-phosphate (Glc6P), 6-phosphogluconolactone, or 6-phosphogluconate was added. Assumptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…The proximity of these two enzymes suggests that they form a supramolecular complex or metabolon within cells. This suggestion is in agreement with a previous biochemical study in plant and yeast systems using radiolabeled substrates that showed substrate channeling in the HMS (46). Hence, supramolecular complex formation explains FIGURE 11.…”
Section: Discussionsupporting
confidence: 93%
“…The proximity of these two enzymes suggests that they form a supramolecular complex or metabolon within cells. This suggestion is in agreement with a previous biochemical study in plant and yeast systems using radiolabeled substrates that showed substrate channeling in the HMS (46). Hence, supramolecular complex formation explains FIGURE 11.…”
Section: Discussionsupporting
confidence: 93%
“…/mben.2002 hydrolysis of the intermediate 6-phosphoglucono-d-lactone to 6-phosphogluconate (Debnam et al, 1997;Levy, 1979), and in line with our previous publication on this subject (Moritz et al, 2000), we feel it is safe to assume that the glucose-6-phosphate dehydrogenase is in fact the ratecontrolling step of the oxidative part of the pentose phosphate pathway (Greenbaum et al, 1971;Gumaa and Mc Lean, 1969). Therefore only this enzyme is considered in the following discussions on PPP flux.…”
Section: Discussionmentioning
confidence: 76%
“…They found evidence of complexes between g3p dehydrogenase, transketolase, and transaldolase. Debnam et al (1997) concluded from their research that intermediates of the oxidative branch of the PPP are channeled between hexokinase, g6p dehydrogenase, and 6pg dehydrogenase. Further channeling complexes have been suggested between aldolase and glycerol phosphate dehydrogenase, between aspartate aminotransferase and glutamate dehydrogenase (Ova di, 1990), and between the enzymes of the tricarboxylic acid cycle (Haggie et al, 1999).…”
Section: Pitfall Ii: Microcompartmentation Due To Metabolite Channelingmentioning
confidence: 97%